Successful Control of Acute Myelofibrosis with Lenalidomide. (4th January 2011) - Vassilopoulos, G.; Palassopoulou, M.; Zisaki, K.; Befani, M.; Bouronikou, E.; Giannakoulas, N.; Stathopoulou, E.; Matsouka, P.
Abstract : Acute panmyelosis with myelofibrosis (APMF) is a rare, fatal hematological neoplasm that is characterized by the acute onset of cytopenias and fibrosis in the bone marrow in the absence of splenomegaly or fibrosis-related morphological changes in the RBCs. We present the case of a 59-year-old female who presented with a two-month history of anemia, leucopenia and a normal platelet count. The marrow was heavily fibrotic, and no aspirate material could be obtained; the biopsy showed extensive infiltration with small to medium size megakaryocytes, dysplastic changes in the erythroid compartment, and left shift in the myeloid cells. The patient was treated for four months with anabolic steroids (Danazol), growth factors and received regular blood transfusions. At 4 months after diagnosis, the patient was started on Lenalidomide, 10 mg/day for a 21-d-course along with growth factor support. At 6 months after treatment, the patient was transfusion-independent, had normalized blood counts, and, at 32 months on continuous lenalidomide treatment, her needs for growth factor support have been minimized. Repeat bone marrow biopsies showed a patchy distribution of fibrosis with areas of normal cellularity and morphology. To our knowledge, this is the first case for a medication that could reverse the fatal outcome of APMF.